2001
DOI: 10.1038/35051029
|View full text |Cite
|
Sign up to set email alerts
|

A massive reservoir of low-excitation molecular gas at high redshift

Abstract: Molecular hydrogen (H 2 ) is an important component of galaxies because it fuels star formation and accretion onto active galactic nuclei (AGN), the two processes that generate the large infrared luminosities of gas-rich galaxies 1,2 .Observations of spectral-line emission from the tracer molecule carbon monoxide (CO) are used to probe the properties of this gas. But the lines that have been studied in the local Universe -mostly the lower rotational transitions of J = 1 → 0 and J = 2 → 1 -have hitherto been un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(115 citation statements)
references
References 21 publications
9
104
2
Order By: Relevance
“…With a low threshold for excitation, requiring n(H 2 ) $ 10 2 cm À3 and ÁE/k $ 5 K, CO (1!0) emission ( rest ¼ 115:271 GHz) is the most representative tracer of the metal-enriched molecular gas mass in galaxies because it is sensitive to the cold, diffuse gas that may dominate. Papadopoulos & Ivison (2002) and Greve et al (2003) presented evidence for large amounts of cold, low-excitation gas at high redshift, as first suggested by Papadopoulos et al (2001), in the galaxy HR 10. In this submillimeter-bright extremely red object (ERO) that lacks obvious AGN signatures, at z CO ¼ 1:439, the CO (5!4) line luminosity underestimates the cold molecular gas mass by nearly an order of magnitude.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…With a low threshold for excitation, requiring n(H 2 ) $ 10 2 cm À3 and ÁE/k $ 5 K, CO (1!0) emission ( rest ¼ 115:271 GHz) is the most representative tracer of the metal-enriched molecular gas mass in galaxies because it is sensitive to the cold, diffuse gas that may dominate. Papadopoulos & Ivison (2002) and Greve et al (2003) presented evidence for large amounts of cold, low-excitation gas at high redshift, as first suggested by Papadopoulos et al (2001), in the galaxy HR 10. In this submillimeter-bright extremely red object (ERO) that lacks obvious AGN signatures, at z CO ¼ 1:439, the CO (5!4) line luminosity underestimates the cold molecular gas mass by nearly an order of magnitude.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies of CO (1!0) emission from high-z galaxies have been carried out with the Very Large Array ( VLA; e.g., Papadopoulos et al 2001;Carilli et al 2002b;Greve et al 2003Greve et al , 2004. The Robert C. Byrd Green Bank Telescope (GBT) far exceeds the current capabilities of the VLA in instantaneous spectral bandwidth (800 MHz maximum per spectrometer bank, compared with 50 MHz at the VLA) with a comparable effective collecting area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher amount of M H 2 as denoted by the higher value of α in these massive galaxies might be possible. For example, the presence of large amounts of cold and low-excited molecular gas have been suggested by Papadopoulos et al (2001) for the QSO APM 08279+5255 at z = 3.91.…”
Section: Individual Qsos At Zmentioning
confidence: 99%
“…In addition to the high excitation CO observations at z = 6.4 (Bertoldi et al 2003) this molecule has also been observed in for example a damped Lyman-α system at z = 2.4 (Srianand et al 2008) and in a field containing an over-density of Lyman break galaxies at z = 5.1 (Stanway et al 2008). A massive CO reservoir has also been detected at z = 3.9 (Papadopoulos et al 2001). An unusually high amount of neutral hydrogen was found by Frye et al (2008) in a 14 Mpc region surrounding a young galaxy at z = 4.9.…”
Section: Interesting Speciesmentioning
confidence: 82%